(untitled) (Acta Scientiarum. Biological Sciences, 2025)
The Neotropical River otter (Lontra longicaudis) is a mustelid primarily characterized by natatorial locomotion, which enables it to inhabit humid forests, swamps, and savannas from Mexico to northern Argentina. Anatomical information on this species remains scarce. Therefore, this study aimed to describe the craniolateral antebrachial muscles of this species. We examined a juvenile specimen fixed in 10% formaldehyde. The brachioradialis muscle was strongly developed and originated from the neck of the humerus. The extensor carpi radialis muscle consisted distally of two bellies inserting onto metacarpal bones II and III. The extensor digitorum communis muscle sent tendons to the digits II-V, whereas the extensor digitorum lateralis muscle sent tendons to digits III-V. The extensor carpi ulnaris muscle had two heads, one humeral and one ulnar. The extensor digiti I et II muscle sent a double tendinous fascicle to the digit II. The anatomical arrangement of the craniolateral antebrachial muscles of L. longicaudis suggests adaptations for manus movements necessary for semiaquatic locomotion—primarily natatorial—, and for manipulating its food.